Occupational exposure, respiratory health and sensitisation among crab processing workers. A study among processors of king crab (Paralithodes camtschaticus) and edible crab (Cancer pagurus) in Norwegian land based crab processing plants. - Thomassen, Marte Renate (UiT The Arctic University of Norway, 2017)
The papers II and IV of this thesis are not available in Munin. Paper II: Thomassen, M. R., Kamath, S. D., Lopata, A. L., Madsen, A. M., Eduard, W., Bang, B. E., Aasmoe, L.: “Occupational Exposure to Bioaerosols in Norwegian Crab Processing Plants”. Available in Ann Occup Hyg 2016, 60(7):781-94. Paper IV: Thomassen, M. R., Kamath, S. D., Bang, B. E., Lopata, A. L., Aasmoe, L.: “Allergic sensitisation among Norwegian king crab (Paralithodes camtschaticus) and edible crab (Cancer pagurus) processing workers and identification of major allergenic proteins”. (Manuscript). Occupational asthma and allergy are health problems found in the seafood processing industry. The aim of this thesis was to investigate the exposure to central components in bioaerosols collected in the breathing zone of crab processing workers, and explore the workers’ prevalence of respiratory symptoms and sensitisation to crustacean allergens. This thesis describes the exposure levels of total protein, tropomyosin, trypsin, NAGase and endotoxin in king crab and edible crab processing plants. This work establishes that both king crab and edible crab processing workers are exposed to bioaerosols containing these components. When comparing king crab and edible crab processing, king crab processing results in highest levels of endotoxin while edible crab processing has the highest levels of tropomyosin and total protein. Differences in exposure levels between the king crab processing plants suggesting a plant effect where local differences in production, ventilation and plant layout is important for the exposure to bioaerosols. This work also describes the increased prevalence of respiratory symptoms among crab processing workers compared to a non-exposed control group. However, there is little difference between exposed workers and controls in lung function parameters. The control group has an increased prevalence of self-reported asthma and allergy compared to the crab processing workers. Furthermore, this work demonstrates elevated IgE and ...